Unveiling Leptospira prevalence and exposure in sanitation workers, a cross-sectional study in Ningbo City, China - Su, Hui; Xu, Keye; Wang, Wuke; Liu, Yuhui; Ping, Guohua; Bo, Dingyi (Frontiers in Public Health, 2025)
BackgroundThe environmental presence of pathogenic Leptospira species poses a substantial threat to human health. Sanitation workers, due to their frequent exposure to contaminated soil or water, are at an increased risk of infection. This study aimed to better understand the risk factor of leptospirosis, pathogen exposure, and carriage among sanitation workers in Ningbo, so to help prevent and manage future outbreaks.MethodsA total of 306 samples were collected, comprising 102 whole blood samples, 102 serum samples, and 102 urine samples from sanitation workers which were categorized into 3 groups. Serum samples were analyzed using ELISA to detect IgM and IgG antibodies. qPCR targeting lipL32 and sec Y were employed on urine and whole blood samples. PCR were performed targeting sec Y followed by sequencing using Sanger method, alignment using DNASTAR MegAlign and MEGA X. Tested positive bio-samples subsequently cultured in EMJH broth supplemented with 5-fluorouracil to facilitate bacterial growth, and examined using a dark-field microscope.ResultsThe questionnaires results showed long working hours (most frequently reported risk factor 60.78%) and employment in garbage sorting (52.94%) were associated with elevated risk of infection (OR = 1.92 and OR = 1.68; p = 0.004 and p = 0.03, respectively), while use of boots (56.86%), masks (41.18%) and soaps (92.16%) can reduce the risk (OR = 0.33, OR = 0.55 and OR = 0.43; p<0.001, p = 0.03 and p = 0.007, respectively). 59.8% of participants tested positive for IgM. qPCR analysis targeting the sec Y gene revealed a positivity rate of 32.4% in blood samples and 7.8% in urine samples. Notably, the lipL32 gene was not detected in any samples. 42 secY gene amplicons obtained from whole blood samples and 8 from urine samples exhibited high sequence similarity to Leptospira interrogans (L. interrogans) when analyzed using DNASTAR MegAlign, clustering with L. interrogans (GenBank accession number OM456545.1). However, culture results showed negative through 2 months observation.ConclusionThis observation indicates the prevalence of a pathogenic L. interrogans subtype, which lacks the lipL32 gene, among asymptomatic sanitation workers. It is imperative for these workers to possess knowledge about infection risks and preventive measures to mitigate the likelihood of infection.